2017
DOI: 10.1080/13506129.2017.1301419
|View full text |Cite
|
Sign up to set email alerts
|

Tafamidis delays disease progression in patients with early stage transthyretin familial amyloid polyneuropathy: additional supportive analyses from the pivotal trial

Abstract: NCT00409175.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 22 publications
2
34
0
Order By: Relevance
“…Previous studies also reported improvements over the long term after LT in the mPND score, sensory and motor disturbances of some patients [18], and tissue-deposited amyloid regression has also been described [19,36]. Tafamidis, a transthyretin stabilizer, has been shown to delay disease progression during an 18month, double-blind, placebo-controlled randomized trial, including 128 early affected patients with hATTR V30M [23,37]. Long-term effects of tafamidis therapy demonstrated good tolerability and persistent reduction in the disease progression rate [24,25].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies also reported improvements over the long term after LT in the mPND score, sensory and motor disturbances of some patients [18], and tissue-deposited amyloid regression has also been described [19,36]. Tafamidis, a transthyretin stabilizer, has been shown to delay disease progression during an 18month, double-blind, placebo-controlled randomized trial, including 128 early affected patients with hATTR V30M [23,37]. Long-term effects of tafamidis therapy demonstrated good tolerability and persistent reduction in the disease progression rate [24,25].…”
Section: Discussionmentioning
confidence: 91%
“…Tafamidis, a transthyretin stabilizer, has been shown to delay disease progression during an 18‐month, double‐blind, placebo‐controlled randomized trial, including 128 early affected patients with hATTR V30M . Long‐term effects of tafamidis therapy demonstrated good tolerability and persistent reduction in the disease progression rate .…”
Section: Discussionmentioning
confidence: 99%
“…The administration of 'pharmacological chaperones', which stabilize the native conformation of a mutant enzyme and thus shift the folding balance away from degradation and aggregation, is being used in a clinical trial for lysosomal storage diseases (NCT00433147). Similarly, small molecules that stabilize the folded, functional state of a protein are being used in clinical trials to misassemble toxic amyloid aggregates 174 . Proteostasis can also be regulated by altering the composition of the chaperone network using small interfering RNAs (siRNAs) or compounds such as diltiazem and verapamil, both of which are Ca 2+ channel blockers, to decrease intracytoplasmic Ca 2+ levels.…”
Section: Targets and Therapeutic Interventions For Insufficient Protementioning
confidence: 99%
“…This type of evidence nourishes disease awareness, avoiding/reducing misdiagnosis of the disease [11], which can delay disease-modifying treatments, all more effective in early disease stages [9,12]. This study aims to estimate the incidence and prevalence of TTR-FAP in Portugal and to describe patients' demographic characteristics.…”
Section: Introductionmentioning
confidence: 99%